Variation in Incidence of Pediatric Crohn's Disease in Relation to Latitude and Ambient Ultraviolet Radiation: A Systematic Review and Analysis. Issue 4 (April 2015) - Holmes, Elizabeth A.; Xiang, Fan; Lucas, Robyn M.
Abstract : Background: Pediatric Crohn's disease (CD) is a lifelong, debilitating, and costly disease. In previous studies, CD incidence increased with higher geographic latitude in the Northern Hemisphere. This may indicate a role for lower vitamin D status as a risk factor for CD. Analysis of worldwide incidence of pediatric CD has not been previously reported. Methods: We undertook a systematic review of population-based studies reporting incidence of pediatric CD and published between 2003 and 2013. Included studies had well-defined diagnostic criteria for CD, evidence of high case ascertainment, reported incidence according to age group, and provided a specific location. Average daily ambient ultraviolet radiation (UVR) for each location was derived from satellite data. Negative binomial regression was used to assess the association between pediatric CD incidence and latitude and ambient UVR, adjusting for the study year. Results: Twenty-eight articles provided 39 incidence data points. Incidence of pediatric CD increased with higher latitude, and in association with a greater number of months where the average daily UVR was lower than a previously published threshold of 1.488 kJ/m 2 . Incidence of pediatric CD increased over calendar time. Conclusions: After applying rigorous quality assessment criteria, and including only population-based studies, there was a modest increase in incidence of pediatric CD with higher latitude and greater number of months with low ambient UVR. Reporting using nonconsistent diagnostic criteria and age groups, with poorly defined geographic locations, makes it difficult to compare data across different studies. Abstract : Article first published online 26 February 2015.Supplemental Digital Content is Available in the Text.